MVRDV : Pabellón de la biodiversidad (2002)
Proyecto de renovación urbana en Barcelona con motivo del <Fórum>
Keywords: MAAS, WINY; RIJS, JACOB VAN; VRIES, NATHALIE DE; BARCELONA; ESPAÑA; PABELLONES; EXPOSICIONES; PROYECTOS